The Influence of Product Completeness and Word of Mouth on Consumer Purchase Interest at Aziz Bontang Bookstore - Sari, Ayu Dita; Aulia, Karimatul (Universitas Muhammadiyah Palu, 2025)
This research was conducted to determine the influence of Product Completeness and Word of Mouth on Purchase Interest at the Aziz Bontang Bookstore. This research method is descriptive-quantitative, using data collection techniques such as observation, documentation, questionnaires and interviews. The respondents of this research were 100 respondents, namely consumers who had purchased and used Aziz Bontang Bookstore products. The analysis technique used is multiple linear regression with the SPSS version 16 application. The results of the research show that from the results of the partial test or T test on Product Completeness, results are tcount 4.931 > ttable 1.984 and word of mouth are tcount 8.062 > ttable 1.984 with a significance of 0.00 < 0, 05. The results of the simultaneous test or Ftest in this study obtained Fcount of 169.040 > Ftable 3.09 with a significance of 0.00 < 0.05. From the results of the T Test and F Test, it is known that the Product Completeness and Word of Mouth have a significant effect. on purchasing interest at the Aziz Bontang Bookstore.